Insertional Achilles tendinopathy is associated with arthritic changes of the posterior calcaneal cartilage: a retrospective study. Issue 1 (December 2015) - Palmanovich, Ezequiel; Oshri, Yael; Brin, Yaron; Edelshtein, Evgeny; Nyska, Meir; Hetsroni, Iftach
Abstract Background To characterize the histological changes within the posterior calcaneal cartilage in patients with insertional Achilles tendinopathy (IAT) and test the relationships between severity of the histological changes and level of functional impairment. Methods Sixteen posterior calcaneal wall specimens of patients with IAT who had posterior calcaneal ostectomy were investigated. Hematoxylin-eosin stain, Toluidine-blue stain, Polarized light microscopy, and Masson Trichrome stain were used to characterize histological changes. Changes within the posterior calcaneal wall cartilage were graded according to Osteoarthritis Research Society International (OARSI) criteria. Functional scores were completed at the time of surgery according to the American Orthopedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot score. Results Mean age of patients was 48.9 years. Histological findings within the posterior calcaneal wall cartilage specimens were consistent with arthritic changes. OARSI grading indicated Grade 2 changes in one specimen, mean AOFAS score 60; Grade 3 changes in three specimens, AOFAS score 73.7 ± 2.5; Grade 4 changes in four specimens, AOFAS score 44 ± 21.4; Grade 5 changes in eight specimens, AOFAS score 48 ± 9.9. Higher OARSI grades were correlated with lower AOFAS scores (rho  = −0.65, p  < 0.01). Conclusions Degenerative arthritic changes of the posterior calcaneal wall cartilage characterize patients with IAT and the severity of such changes is directly correlated to the degree of functional impairment.